Exploring ESG challenges and opportunities navigating towards a better future - Grima, Simon (Emerald Publishing, 2025)
The number of companies that are adopting sustainability strategies and disclosing information related to Environmental, Social and Corporate governance (ESG) issues is on the rise. This special volume encapsulates the transformative journey businesses undertake to balance profitability with responsibility
Description based on publisher supplied metadata and other sources
Keywords: Environmental, Social and Governance